DILEMA STRATEGIS KONFLIK INDIA-PAKISTAN DALAM BAYANG-BAYANG PATRONASE AMERIKA SERIKAT DAN TIONGKOK - Ningrum, Putri Ayu; Suharman , Yoga (Jurnal Studi Diplomasi dan Keamanan, 2026)
The conflict between India and Pakistan has been going on for more than a decade and has intensified in recent years. In the context of contemporary geopolitics, this dispute reflects the dilemmas and complexities of the foreign policy of developing countries seeking to navigate their interests amid rivalries between major powers. This article examines the dynamics of the India-Pakistan conflict using the concept of the prisoner's dilemma in the framework of game theory to understand how rational calculations and limited trust shape the behavior of both countries. In this analysis, the external involvement of Tiongkok and the United States is seen as a complementary variable that strengthens the incentives for both countries to maintain non-cooperative strategies for short-term national goals. This situation shows that the foreign policy orientation practiced by developing countries is often influenced by the distribution of power at the international level, which limits regional cohesion. This article contributes to expanding the study of international relations in South Asia, particularly in understanding how the involvement of extra-regional powers and strategic rationality shape foreign policy behavior in the protracted conflict between India and Pakistan. Keywords: United States, India-Pakistan, Developing countries’ foreign policy, Prisoner’s dilemma, Tiongkok.